Effects of permissive hypercapnia on intraoperative cerebral oxygenation and early postoperative cognitive function in elderly patients undergoing laparoscopic surgery - Chen, Huixian; Yu, Yingqun; Huo, Jiang; Dou, Guijin; Zhao, Qianqian; Zhao, Shuang; Zhao, Fuqi (Frontiers in Medicine, 2025)
BackgroundThis study examines the effect of permissive hypercapnia (PH) on cerebral oxygenation (rSO2) and early postoperative cognitive function in elderly patients (EP) undergoing laparoscopic surgery (LS).MethodsThis retrospective study analyzed data from elderly patients who underwent laparoscopic surgery with PH mechanical ventilation or conventional ventilation (CV) ventilation strategies between 2019 and 2024. The individuals were separated into two groups as stated by the intraoperative anesthesia method, and equal numbers in each group. A total of 550 patients were initially screened for eligibility, of whom 100 were excluded based on predefined criteria. The final analysis included 450 patients, with 225 receiving PH mechanical ventilation (PH group) and 225 receiving conventional ventilation (CV, control group). Postoperative cognitive dysfunction (POCD), postoperative regional cerebral oxygen saturation (rSO2), and cognitive function (measured by the Mini-Mental State Examination, MMSE) were compared involving the two groupings. Secondary outcomes included postoperative recovery time, bed rest time, hospital stay, postoperative complications, and intraoperative vital signs (blood pressure, heart rate, and arterial partial pressure of carbon dioxide).ResultsPermissive hypercapnia was associated with significantly improved intraoperative cerebral oxygenation (rSO2) compared to conventional ventilation (mean difference 4.62%, 95% CI 3.81–5.43; P < 0.001), particularly following pneumoperitoneum establishment. MMSE scores demonstrated less pronounced decline at postoperative day 1 in the PH group (23.05 ± 0.23) versus controls (20.67 ± 1.63; P < 0.001), with recovery to baseline by day 14 (24.87 ± 1.23 vs. 23.91 ± 1.51; P = 0.012), with MMSE scores higher than those in the CV group (P < 0.05). Secondary outcomes, including recovery time and vital signs, did not differ significantly between groups (P > 0.05).ConclusionPermissive hypercapnia significantly improves rSO2 and was associated with smaller early declines in MMSE scores, suggesting a potential benefit on global cognition. These findings are exploratory and should be confirmed using comprehensive neuropsychological batteries.